Cultural Interaction of Bengkulu City Communities with Muhammadiyah Education in History Context - Dedy Novriadi; Siti Misbah; Syubli Syubli; Nilda Susilawati (Islam Transformatif : Journal of Islamic Studies, 2024)
Abstract This research aims to analyze the interaction between the culture of the people of Bengkulu City and Muhammadiyah education from a historical perspective, especially related to the controversy over the acceptance of religious purification teachings and the contribution of Muhammadiyah education to traditions that have long existed in society. This research was carried out using a historical approach through information from the figures involved and knowing the history of the development of Muhammadiyah education in Bengkulu City and several other primary and secondary sources. The study results found that Muhammadiyah education in Bengkulu City began with a debate between Muhammadiyah figures and kaum tuo (the old generation). Muhammadiyah's teachings focus on the purification of Islamic teachings in the culture of the Bengkulu City community, which contained many mystical and polytheistic (shirk) elements. Finally, the approach of Muhammadiyah figures led to cultural interaction with Islamic teachings as long as they did not conflict with Islamic teachings in religious activities, death, marriage, art, music, and curriculum in Muhammadiyah educational institutions through local cultural content. This research has implications for developing a curriculum based on local cultural values ​​so that it can improve character and identity among students.   Abstrak Tujuan penelitian ini adalah untuk menganalisis interaksi antara budaya masyarakat Kota Bengkulu dengan pendidikan Muhammadiyah dalam perspektif sejarah, khususnya terkait dengan kontroversi penerimaan ajaran pemurnian agama dan kontibusi pendidikan Muhammadiyah terhadap tradisi yang telah lama ada di masyarakat. Penelitian ini dilakukan dengan menggunakan pendekatan sejarah melalui informasi dari tokoh-tokoh yang terlibat dan mengetahui sejarah perkembangan pendidikan Muhammadiyah di Kota Bengkulu dan beberapa sumber primer dan sekunder lainnya. Hasil penelitian menemukan bahwa awal masuknya pendidikan muhammadiyah di Kota Bengkulu menjadi perdebatan antara tokoh muhammmadiyah dan kaum tuo (generasi tua) karena ajaran Muhammadiyah menginginkan adanya pemurnian ajaran Islam pada budaya masyarakat Kota Bengkulu yang banyak mengandung unsur mistik dan kesyirikan, dengan pendekatan tokoh Muhammadiyah akhirnya terjadi interaksi budaya dengan ajaran Islam sepanjang tidak bertentangan dengan ajaran Islam dalam aktivitas keagamaan, kematian, perkawinan seni, musik dan kurikulum di lembaga pendidikan muhammadiyah melalui muatan budaya lokal. Penelitian ini berimplikasi pada pengembangan kurikulum yang berbasis nilai budaya lokal agar mampu meningkatkan karakter dan identitas di kalangan siswa.